Spiritual Leadership within An Army Acquisition Program Management Context - Novikov, Valentin (Journal of Leadership, Accountability and Ethics, 2017)
Although the leadership style of a program manager effects the success of the project (Muller & Turner, 2007), unfortunately, the typical program manager primarily focuses on project cost, schedule and performance constraints. Since program management leadership is often overlooked, this generates the question on what types of leadership may be effective. Consequently, a qualitative study was conducted to examine the possible appropriateness of spiritual leadership within the Department of the Army acquisition program management context since the characteristics of spiritual leadership as described by Fry (2003) engenders calling and membership leading to the outcomes of organizational commitment and productivity.